KUALITAS SPERMATOZOA DAN BERAT ORGAN REPRODUKSI MENCIT (Mus musculus) SETELAH PEMBERIAN EKSTRAK BIJI KLABET (Trigonella foenum-graecum L.) - Maulidya Rosa Putri Utama; Dwi Ariani Yulihastuti; Sang Ketut Sudirga (SIMBIOSIS, 2024)
Indonesia is one of the countries known to have the highest biodiversity in the world. There are 18 types of herbs that have the potential as antifertility in men, one of which is the klabet plant or fenugreek. Klabet is believed by ordinary people to have properties to increase the production and quality of spermatozoa. According to previous research klabet has toxic effects that can inhibit fertility due to the content of phytochemicals in it. This study aims to determine the effect of fenugreek seed extract on the quality of spermatozoa and the weight of the reproductive organs of mice. The mice used were 20 male mice weighing about 25-30 grams divided into 4 treatments namely control (P0), 56 mg/kgBB (P1), 112 mg/kgBB (P2), 168 mg/kgBB (P3) with 5 repetitions. Giving treatment for 24 days. The method used is RAL (Complete Randomized Design) and the resulting data is analyzed using ANOVA. The parameters studied were testicular weight, epididymis weight, motility, morphology and number of male mouse spermatozoa. The results showed that there was a real difference (p≤0.05) between the control and treatment of the klabet seed extract on the quality of spermatozoa and the weight of the testicle but not significantly different (p≥0.05) to the weight of the epididyimis. Concentration of mice spermatozoa decreased by 10.60%, progressive spermatozoa motility decreased by 55.61%, nomal morphology decreased by 57.92%, while testicular weight decreased by 38.46%. The most effective dose of fenugreek seed extract used as an antifertility agent was a dose of 168 mg/kgBW (P3).